Molecular cloning and functional characterisation of duck (Anas platyrhynchos) tumour necrosis factor receptor-associated factor 3. Issue 4 (4th July 2019) - Zhou, Y.; Zhou, Y.; Kang, X.; Meng, C.; Zhang, R.; Guo, Y.; Xiong, D.; Song, L.; Jiao, X.; Pan, Z.
ABSTRACT: 1. Tumour necrosis factor receptor-associated factor 3 (TRAF3) is a key regulator of innate immunity and acquired immunity, and has a salient anti-viral role. 2. In this experiment, the duck TRAF3 ( DuTRAF3 ) gene was cloned according to the Anas platyrhynchos TRAF3 sequence to explore its function. The TRAF3 open reading frame contains 1704 bp that encode a protein of 567 amino acids, which contain a RING finger domain, two zinc finger motifs, a coiled-coil region, and a MATH domain. 3. Reverse transcription-polymerase chain reaction showed that DuTRAF3 was expressed in all the examined tissues, with a comparatively higher expression in the spleen and brain tissues. 4. In HEK293T cells, DuTRAF3 overexpression resulted in a significantly increased NF-κB activity and interferon (IFN)-β promoter activation. 5. Following resiquimod (R848) and poly(I:C) stimulation of duck peripheral blood mononuclear cells (PBMCs), the expressions of TRAF3 and IFN-β were significantly upregulated; in addition, following R848 stimulation, the mRNA levels of IL-6, IL-8 and IL-10 were also significantly upregulated. After infection with the Newcastle Disease Virus LaSota vaccine strain, the mRNA levels of IL-6 and IL-10 were significantly upregulated, while that of TRAF3 was downregulated. 6. These results suggest that DuTRAF3 has an important role to play in innate antiviral immune responses.